PENGARUH MEDIA TANAH PASCA PANEN TANAMAN LEGUMINOCEAE TERHADAP PERTUMBUHAN TANAMAN KANGKUNG (Ipomea reptans L. Poir.) SEBAGAI SUMBER BELAJAR BIOLOGI - Danny Azhari; Handoko Santoso; Triana Asih (EDUBIOLOCK, 2020)
The aim of this research was 1) to determine the effect of variations in post-harvest soil planting media of Leguminoceae on kale plant growth, 2) to determine the utilization of yield as learning resources in biology. This type of research is an experimental study using a completely randomized design (CRD). There were 4 treatments in this study, 3 treatments giving different types of planting media post-harvest leguminoceae (post-harvest peanut soil (Arachys hypogea), post-harvest long bean (Vigna sinensis) and a combination of post-harvest groundnut media (Arachys hypogea ) + post-harvest long bean (Vigna sinensis), each root is given each repetition. The parameters observed in this study were height (cm), number of leaf blades, and wet weight (grams) of spinach plants produced. Based on the results of research it can be concluded that there is a significant effect of post-harvest soil media on Leguminoceae plants on growth of water spinach plants, including plant height, number of leaves and wet weight of spinach plants, the results of research based on test analysis of the critical walles is x2hit> x2daf.Further tests showed variations in the type of planting media that had the most optimum influence on the growth of water spinach plants was the type of soil planting media after harvesting peanuts. The results of this study can be used as a source of biology learning for Class X high school monera kingdim material in the form of brochures.